A Conceptual Framework for Mentoring in a Learning Organization. (November 2015) - Klinge, Carolyn M.
The purpose of this article is to provide a conceptual framework for mentoring as an added component of a learning organization in the context of adult learning and development theories. Mentoring is traditionally a process in which an experienced person (the mentor) guides another person (the mentee or protégé) in the development of her or his own ideas, learning, and personal/professional competence. Mentoring uses transformational theory through critical reflection in a non-judgmental manner and addresses the andragogical principle that experience is the richest source for adult learning. In a learning organization, adult development is fostered for both mentee and mentor in a reciprocal and collaborative learning partnership. Critical issues in designing a mentoring program for facilitating the development of a sustainable learning organization are discussed with potential pitfalls. Anticipated outcomes from a mentoring program in a learning organization include application of new knowledge in daily tasks, individual and collaborative analysis of problems and possible solutions, evaluation of new technologies or strategies and determination of their utility, and the creation of new business plans for the learning organization.